Why Citizen Kane was unhappy: Motive‐Goal Incongruence. Issue 8 (August 2017) - Hofer, Jan; Busch, Holger
Abstract: Why do some people benefit more from successfully pursuing their goals than others? Motivational psychology has recently come up with an answer to this question: People differ in the extent to which their goals are aligned with their implicit motives. That is, on a conscious level, people may strive for, for example, achievement goals although on an unconscious level their implicit achievement motive is low. In such a case of motive–goal incongruence, pursuit and realization of achievement goals are associated with little or no well‐being. On the other hand, for people whose conscious goals and implicit motives are congruent, goal progress is strongly associated with well‐being. Legendary movie character Charles Foster Kane from Citizen Kane illustrates this dilemma: Constantly pursuing and realizing power goals, he does not succeed in satisfying his affiliation‐intimacy motive – and finally dies an unhappy man. The present article reviews what is known about the causes and effects of motive–goal congruence. In doing so, open questions are raised that future research ought to address.